Pre-professional practice according to ISO 21001 STANDARDS in a study program of a Peruvian public university. - Gallardo Ramírez, Jessica Natalí (2023)
As of the validity of the New University Law 30220, the university quality assurance policy is applied, marking a milestone for the verification and supervision of basic quality conditions, in the case of teachers in training at the initial level of education no It has been the exception, and the implementation of the missionary process of the Pre-professional Practice has been designed in the study, in such a way that a value is generated at a pedagogical, institutional and social level. To achieve the objective, the study was developed with a mixed approach and a pre-experimental design that allowed to show the benefits of the research, obtaining results of significant improvement in the satisfaction of the students who take the Practice course by applying the T-Student test that gave a value of 4.860, which generated a p = 0.000 value lower than 0.05. Thus concluding that the implementation of a missionary process under quality standards in accordance with the requirements of the International Standard ISO 21001 and aligned with the profile of the professional of an initial education study program guarantees the ideal training in the teachers of tomorrow.